Selection index for Duroc pigs based on average daily gain, feed conversion ratio, and intramuscular fat content - Sang Van Le (Vietnam Journal of Science, Technology and Engineering, 2023)
This study was conducted to compare the genetic gain per sow per year of Duroc pigs in twelve scenarios. These scenarios were based on the number of traits used such as average daily gain (ADG), feed conversion ratio (FCR), intramuscular fat content (IMF) and were also based on the number of records of phenotype for these traits from the individual animal and its relatives. The values of all relevant genetic and economic parameters were selected from the literature and applied to the magnetotail (MT) index model to calculate the index selection accuracy and response per trait. Genetic gain per sow per year was calculated based on a farm with 400 Duroc sows. The results showed that the economic value of FCR was much larger than the economic value of ADG and IMF. The selection response in units of ADG was higher when using phenotypes measured using ADG and FCR only while selection response per unit of IMF was the opposite. The economic weight of the response for IMF using three traits (ADG, FCR, and IMF) information was doubled when using ADG and FCR trait information. The standard deviation (SD) index and genetic gain per year when using information from the three traits were higher than those when using information from ADG and FCR. Within the same number of traits measured, the genetic gain per sow per year was highest at $568.05 when using information of the three traits from the individual animal’ s phenotype and their progeny . It was the lowest at $473.06 when using ADG and FCR information from only the animal itself.